2021
DOI: 10.1016/j.omto.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of lncRNAs as biomarkers for diagnosis, prognosis, and treatment response in clear cell renal cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common histological type of renal carcinoma and has a high recurrence rate and poor outcome. Accurate patient risk stratification based on genetic markers can help to identify the high-risk patient for early and further treatments and would promote patient survival. Long non-coding RNAs (lncRNAs) have attracted widespread attention as biomarkers for early diagnosis, treatment, and prognosis because of their high specificity and sensitivity. Here, we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
(199 reference statements)
0
3
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) have emerged as promising biomarkers, since they modulate genes at various levels, from epigenetics to post-transcription [11]. In line with other recent publications [12,13], the comprehensive review by Rysz and colleagues describes the roles of specific lncRNAs in RCC and suggests their potential as diagnostic and prognostic markers. Understanding the intricate mechanisms by which lncRNAs influence the disease progression in RCC is essential for the development of targeted therapies that can improve patient outcome [14].…”
mentioning
confidence: 89%
“…Long non-coding RNAs (lncRNAs) have emerged as promising biomarkers, since they modulate genes at various levels, from epigenetics to post-transcription [11]. In line with other recent publications [12,13], the comprehensive review by Rysz and colleagues describes the roles of specific lncRNAs in RCC and suggests their potential as diagnostic and prognostic markers. Understanding the intricate mechanisms by which lncRNAs influence the disease progression in RCC is essential for the development of targeted therapies that can improve patient outcome [14].…”
mentioning
confidence: 89%
“…Despite specific enhancement modes for KIRC, misdiagnosis consistently happens in clinical settings (37), imposing a socio-economic burden on healthcare systems globally. Myriads of studies have identified novel diagnostic biomarkers for kidney cancer, spanning long non-coding RNAs, circulating tumor DNA, and circulating tumor cells; despite this, there is still scope for improvement in specificity as well as sensitivity, and the clinical applicability of such emerging biomarkers remains to be further validated (38)(39)(40)(41). It is inspiring that blood platelet and blood-derived exosome-based polygenic models manifested excellent diagnostic efficacy, offering an accessible complement to existing screening modalities (42-44).…”
Section: B C Amentioning
confidence: 99%
“…Clear cell renal cell carcinoma (ccRCC) acts as the dominant histological subtype of renal cell carcinoma, accounting for around 75–85% of all subtypes 3 , 4 . The clinical outcomes of ccRCC patients after surgical excision is moderate, but the 5-year overall survival rate dramatically diminishes in metastasis or recurrence ccRCC patients 5 , 6 . These advanced ccRCC patients, estimated to be around 30% of all ccRCC patients, show their inefficiency upon traditional chemotherapies and radiotherapies, but they could be somewhat relieved by adjuvant therapy, such as immunotherapies or targeted therapies 3 , 7 .…”
Section: Introductionmentioning
confidence: 99%